Smart PLGA nanoparticles loaded with Quercetin: Cellular uptake and in-vitro anticancer study. (2018) - Halder, Asim; Mukherjee, Pritha; Ghosh, Subarna; Mandal, Saptarshi; Chatterji, Urmi; Mukherjee, Arup
Abstract: Flavonoids have gained attention in cancer chemotherapy due to promising pre-clinical results. Flavonoids are constrained in therapeutics for solubility and permeability limitations. Quercetin (Qr) is a most abundant flavonoid in plants. Smart nanoparticle drug delivery devices were designed for better delivery of Qr. Transferrin was used for nanoparticle ligand tethering for successful particle propagation up to the cancer cell nucleus. PLGA nanoparticles loaded with Qr (QrPLGA) were prepared in modified solvent diffusion method using pluronic as a stabilizer. Transferrin conjugation on QrPLGA (Tf-QrPLGA) was achieved in EDC/NHS coupling reactions. Nanoparticles were characterized in DLS, AFM, TEM and FTIR. In-vitro anticancer efficacy was evaluated in metastatic cancer cell lines. The average particle size in DLS was 150 nm. The entrapment efficiency of Qr (70.52%) and non-fickian release pattern were observed by RP-HPLC. The FTIR analysis confirmed Tf interactions with nanoparticles. Tf-QrPLGA showed significantly strong antiproliferative and cytotoxic effects on both the cancer cell lines. Time-dependent uptake and quantitative count in flow-cytometry showed early time-point intracellular entry of Tf-QrPLGA. Specific cellular localization was confirmed by confocal microscopy. Increased sub-G1 population and decreased G2/M population demonstrating the apoptotic potential and cellular arrest of Tf-QrPLGA on cancer cells.